PENGARUH PENGAWASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MITRA TERA AKURASI JAKARTA SELATAN - Febriani, Alifah; Ratnawati, Whina (Journal of Research and Publication Innovation, 2024)
This study aims to determine and analyze the influence of supervision and discipline on employee performance at PT. Mitra Tera Accuracy addressed Graha Mas Fatmawati Blok A.35, Jl. RS. Fatmawati No.71 South Jakarta. The type of research used is by Quantitative method. The population in the study was 60 people. Data collection techniques by means of questionnaires, observations and literature studies. Data analysis techniques with descriptive methods using Likert scales. The tests used are validity tests, reliability tests, simple linear analysis, multiple linearly, correlation coefficients, determination coefficients, and hypothesis tests. Based on the Partial Test, the work supervision variable (X1) has a calculated value of 2.153 and a significant value of 0.036 and a table value of 2.0024. Because the calculated value of ttable (2.153>2.0024) and the significant value (0.036<0.05), it can be concluded that H0 is rejected and Ha is accepted meaning that there is a positive and significant influence between work supervision variables on employee performance. Strengthened by the value of the coefficient of determination of R square (R2) 0.588, it means that work supervision has a contribution to employee performance. The calculated value of the work discipline variable (X2) is 5.887 is the significance value is 0.000 and the ttable value is 2.0024. because the calculated value of Ttable (5.887>2.002) and the significance value (0.000<0.05) it can be concluded that H0 is rejected and Ha is accepted, meaning that there is a positive and significant influence between work discipline variables on employee performance. Strengthened by the value of the coefficient of determination of R square (R²) 0.723, it means that work discipline has a contribution to employee performance. Based on the results of the f (simultaneous) test, it can be seen that there is a calculation value of 82.618 and a significance value of 0.000. The value of Ftable at the celebration rate of 5% with DFL 2 and DF2 58, then obtained Ftable 3.156. because the fcalculate ftable (82.618>3.156) and significant value (0.000<0.05) so that it can be concluded that the independent variables namely Work Supervision (X1) and Work Discipline (X2) together (simultaneously) have a significant effect on the Employee Performance Variable (Y). Strengthened by the value of the coefficient of determination of R square (R²) 0.744, it means that work supervision and work discipline have a contribution to employee performance